Epistemological Foundations In Philosophy Of Science - Sulaiman, Edi Saputra; Rijal, Syamsul (Al-Fikrah, 2024)
The research objectives are to explore epistemological foundations in the philosophy of science and the steps of the scientific method in epistemology. The research method employed in this study is a literature review (library research). The results of the research indicate that: First, the epistemological foundations in the philosophy of science include empiricism-positivism, rationalism, constructivism, and criticism. Second, the steps of the scientific method in epistemology are referred to as logico hypotetico verificative-deducto hypothetico verificative. This involves a logical framework, formulation of hypotheses, and factual verification, which serve as the basis for scientific truth with openness to new truths.